MONEY AS A TOTAL SOCIAL FACT IN ARGENTINEAN 2001/02 CRISIS AND IN ITS RESOLUTION - Pereira, Jaime Marques (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2011)
This paper opposes to the institutional explanations for sudden reversals of expectations,as was the case in the Argentinean crisis 2001/2002, an analysis revealing a crisis of the trust setin national currency, so conceived as total social fact. Based on this multidimensional view(economic, political and symbolic) of the money functions, we show that the systemic risk of thepublic debt results from the illusions fostered by new classical theory on promises of futureincome founding the political compromises sustaining the currency board monetary regime. Theresolution of this crisis has given room to a more distributive regime inspired in new-keynesiantheory but not to the elimination of this systemic risk. The conclusion points out in the presentcontext of world crisis the more general validity of this issue focusing the responsibility of neoquantitativetheory of money as a representation of economy performing collective action